Drones in Law Enforcement Use for Surveillance Purposes and their Growing Impact on Privacy and Data Protection of Individuals - Hartikainen, Lotta (fi=Turun yliopisto|en=University of Turku|, 2018)
Unmanned aerial vehicles, more commonly known as drones with their advanced technological features are increasingly deployed technology in general but also for law enforcement purposes which is ultimately the scope of the research. Results obtained so far with drone deployments confirm that drones are technically very viable opportunity to be used in law enforcement applications in the field of monitoring and surveillance. The paper establishes how competent authorities may gather a significant amount of personal information in order to maintain public order and prevent crimes, which are seen essential to the national and public interest. Despite of the legitimate purposes, the risk of misuse might occur and thus harsh surveillance measures can strongly inflict with privacy and data protection. Thus, it is argued that a closer and more specific legal framework is needed in the EU in order to respond with possible collision of the fundamental human rights. Consensus on the definition of privacy is definitely facing several contradictions since private and public spheres are becoming more complicated due to the social values and technologies such as drones having impact on them. The relation of such rights as privacy and data protection in the context of surveillance mechanisms create reasonable expectations regarding privacy and its sphere which European Courts have acknowledged. Since drones are a new field to regulate, there does not yet exist any specific Union law regarding law enforcement operations and thus national legislations are quite fragmented. Not many legislative solutions are providing adequate privacy and data protection in context of drones and real-world scenarios. On the other hand, new data protection reform in the EU is soon applicable which tries to answer those challenges created by the increasing exchange of personal data and technological ways to collect this data. The purpose is to provide contribution to the issue where more harmonised and uniform principles are requisite next step in the EU and study the progress which is required to achieve.